Experience of caesarean patients facing their pregnancies and labour in the town of Isiro, Democratic Republic of the Congo - Bwembola, Valentin Boya; Mwimba, Roger Mbungu; Omanyondo, Marie-Claire Ohambe; Bonangaleki, Charles Bokota; Malonga, Djibril Boseane; Bukasa, Augustin Kadiata (Orapuh Journal, 2024)
Introduction Pregnancy and childbirth have historically been considered, both in collective imagination and cultural transmission, as situations that threaten maternal and fetal survival. Purpose This study aims to understand the experiences of women who underwent Caesarean sections at Isiro General Reference Hospital, in relation to their pregnancies and labour, in order to inform precautions for future cases. Methods This is a qualitative study with a phenomenological approach. The population consists of women who underwent Caesarean sections in the gynecology-obstetrics department of Isiro General Reference Hospital. Data were collected through individual, semi-structured face-to-face interviews. Results For most women in the town of Isiro, pregnancy and childbirth are perceived as difficult and painful experiences. They reported discomfort and embarrassment, describing a variety of symptoms that were often mild: various pains, eating and digestion disorders, headaches, shortness of breath, dizziness, etc. In addition, the expectant mothers often felt vulnerable. Conclusion The conception of a child triggers a significant emotional upheaval in women, with psychological and physiological changes, particularly hormonal. These should not obscure the psychological challenges involved. Pregnancy and childbirth represent a period of identity crisis and psychological maturation for the woman transitioning into motherhood.